Translation Assessment of Cultural Legal Terms as Translated from Arabic into English - Hassoon, Ameer Majid; Al-Dahwi, Sameer Salih Mehdi (Al-Adab Journal, 2020)
Culture includes knowledge, belief, art, law, morals, customs and any habits acquired by a Man as a member of society. The cultural differences play a pivotal role in the translation between languages. Preserving the SL cultural values in the translated text constitutes a difficult task for the translator.The present study is a translation assessment of the Arabic cultural legal terms issued by Sharia courts as translated into English. The terms are taken from the book ‘The Reliable Guide to Legal Translation’ written by Adel Azzam Saqf Al-Hait.The problem of the study is that the Arabic Cultural legal terms issued by Sharia courts are inherent in the SL (Arabic language) which make it difficult for the translator to render them into the TL (English language).